AFIKS VERBA DALAM BAHASA SALUAN - Siti Fatinah (Multilingual, 2019)
Affix verbs in the Saluan language can be added to basic word or basic form in the form of verbs, nouns, adjectives, and numerals. The affix has various forms and functions. This study examines the forms and function of verb affixes in the Saluan language. Related with that, this paper aims to describe the forms and function of verb affixes in the Saluan language. The data of this study were obtained using the litterary method. The data is processed using the intralingual equivalent method through a change technique. The results of this study indicate that there are five verb affixes in the Saluan language, namely prefix, suffix, confix, infix, and combinations of affixes. There are nine verb prefixes, namely moN-, pino-, i-, o-, ba-, po-, ko-, maha-, and mompo-. The moN prefix has four allomorphs, namely mom-, mong-, mo-, and mon-. There are  two verb suffixes, namely -onon and-kon. There are four verb confixes, namely kino-an, kina-mo, kina-anmo, and maha-an. The verb infix is only one, namely -in-. Different case with a combination of affixes. The combination of verb affixes is nine, namely moN-akon, moN-kon, moN-i, i-akon, i-kon, pino-akon, pinokon, i-i, -in-an, -in-akon, and iin-kon. There are five functions of the affix form, namely changing the word category in its basic form, forming bitransitive verbs, forming transitive verbs, reciprocal verbs, and forming passive verbs.